2015
DOI: 10.1002/app.43271
|View full text |Cite
|
Sign up to set email alerts
|

Solid state polymerization in a micro‐reactor: The case of poly(tetramethylene terephthalamide)

Abstract: The aim of this work was to develop and optimize a direct solid state polymerization (DSSP) process on a micro scale for alkyldiammonium-terephthalate salts. This was successfully demonstrated for the first time by the case of tetramethylenediammonium-terepththalate salt (4T salt). The derived polymer (PA4T) presents interesting properties, but the temperature-favored acid catalyzed cyclization of tetramethylenediamine (TMD) to mono-functional pyrrolidine and ammonia inhibits a high polymerization conversion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 40 publications
0
26
1
Order By: Relevance
“…The principal peak at 450 °C was due to polyamide decomposition. This decomposition temperature was lower than the reported value of 460 C of PA4T prepared from salts [6].…”
Section: Trang 40contrasting
confidence: 70%
See 1 more Smart Citation
“…The principal peak at 450 °C was due to polyamide decomposition. This decomposition temperature was lower than the reported value of 460 C of PA4T prepared from salts [6].…”
Section: Trang 40contrasting
confidence: 70%
“…A series of semiaromatic polyamide salts were prepared in solution by neutralizing aliphatic diamines of different aliphatic length with terephthalic acid. The obtained semiaromatic salts were further subjected to direct solid state polycondensation that performed in a TGA chamber [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The nucleation stage occurs first on the surface of the crystallites and then in the defective sites. In parallel it has been confirmed that during the initial stages of the DSSP of polyamide salts, the volatile diamine component escapes in both aliphatic (nylon ® ) salts and semi-aromatic polyamide salts [ 20 , 28 , 29 , 32 , 33 ]. In addition, in a DSSP study on PA 66, it was discovered that diamine loss preceded water formation, thus resulting in even more defects in the salt crystal lattice, which in turn are active centers for initiation and propagation [ 20 ].…”
Section: Introductionmentioning
confidence: 98%
“…The direct solid state polymerization (DSSP) of polyamide salts has been systematically investigated in our laboratory since the late 1970s [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. DSSP involves heating the solid reacting mass at a temperature below its melting point and the melting point of the final polymer product under an inert atmosphere as to allow the progression of the polycondensation, while maintaining the solid phase in the reacting mass.…”
Section: Introductionmentioning
confidence: 99%
“…Then, laboratory scale runs in different assemblies were performed so as to confirm the findings from the micro scale. This approach is modeled after the fundamentals of the solid state polycondensation (SSP) of polyamide salts, and lessons from this research field have been adapted in this work [ 27 , 28 , 29 , 30 ]. Thus, a TGA aluminum crucible was used as a micro-scale reactor.…”
Section: Introductionmentioning
confidence: 99%